Kinetic Analysis and Modelling of Cellulose Pyrolysis - Hameed, Samreen (Curtin University, 2019)
Pyrolysis is one of the thermochemical techniques to convert biomass into bio-oil, bio-char and gaseous products. This work has focused on modelling the kinetic behaviour of cellulose, which is the most abundant component in any type of biomass, under slow and fast pyrolysis conditions and in the presence of inorganic species using Distributed Activation Energy Model (DAEM). In addition, cellulose pyrolysis product yield has been estimated using Computational Fluid Dynamics (CFD) modelling framework.